2017
DOI: 10.3390/mi8020050
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Profile Errors of Microlens Surfaces on Laser Beam Homogenization

Abstract: Microlens arrays (MLAs) are key optical components in laser beam homogenization. However, due to imperfect surface profiles resulting from microfabrication, the functionalities of MLAs in beam modulation could be compromised to some extent. In order to address this issue, the effects of surface profile mismatches between ideal and fabricated MLAs on beam homogenization were analyzed. Four types of surface profile errors of MLAs were modeled theoretically and numerical simulations were conducted to quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…However, due to manufacturing deviations in the production process, the MLA surface parameters do not perfectly coincide with the design values, resulting in different local surface errors, such as coordinate distortion [ 15 ], curvature variation [ 16 ], centroid shift [ 33 , 34 , 35 ], or irregular deformation [ 36 ]. We develop three basic error models that contain pitch error, radius-of-curvature error and decenter error, according to the arrangement and geometric features of the MLA used in this paper.…”
Section: Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to manufacturing deviations in the production process, the MLA surface parameters do not perfectly coincide with the design values, resulting in different local surface errors, such as coordinate distortion [ 15 ], curvature variation [ 16 ], centroid shift [ 33 , 34 , 35 ], or irregular deformation [ 36 ]. We develop three basic error models that contain pitch error, radius-of-curvature error and decenter error, according to the arrangement and geometric features of the MLA used in this paper.…”
Section: Modelsmentioning
confidence: 99%
“…In order to effectively utilize the light-field data in the image processing and reconstruction process, the raw image should accurately record the light-field information of the measured target. However, due to manufacturing and assembly defects in the MLAs [ 15 , 16 , 17 ], different distortions appear in the actual images acquired using them, including blurring and aliasing caused by the orientation misalignments between the MLA and the image sensor [ 18 ], as well as changes in brightness, resolution and spot position owing to microlens surface errors [ 19 , 20 ]. The degradation and distortion of the raw image makes a large amount of data information confused or missing, leading to a significant reduction in the reconstruction accuracy and efficiency of the target flow field [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…(3) Quality control of micro systems and processes. Baruffi et al [7] demonstrated the application of the replica molding technology for quality control of micro milled surfaces; Cao et al [8] investigated the effect of profile errors on the surface of micro lenses on laser beam homogenization; Choi et al [9] presented a novel testing platform to characterize and predict the mechanical damage of miniaturized haptic actuator; Gao et al [10] modeled the effect of micro manufacturing process variations on the characteristics of a micro machined doubly-clamped beam.…”
mentioning
confidence: 99%
“…(3) Quality control of micro systems and processes. Baruffi et al [7] demonstrated the application of the replica molding technology for quality control of micro milled surfaces; Cao et al [8] investigated the effect of profile errors on the surface of micro lenses on laser beam homogenization; Choi et al [9] presented a novel testing platform to characterize and predict the mechanical damage of miniaturized haptic actuator; Gao et al [10] modeled the effect of micro manufacturing process variations on the characteristics of a micro machined doubly-clamped beam.…”
mentioning
confidence: 99%